Intelligent Replication Strategy using Neural Network for High Availability in Cloud Environment - Hasni, Noriha; Mohamad, Zarina; Ahmad, Fadhilah; Nor Shuhadah Wan Nik, Wan; Mat Deris, Mustafa (International Journal of Engineering and Technology, 2018)
Cloud computing system has gained its popularity due to its ability to produce efficient data center storage management. Data center has to be available regardless of large amounts of data request. The performance of the system will be degraded if lack of data management in the data center. Data replication is one of the strategies to ensure the data is always available once it is needed. Thus, in this paper will propose an intelligent replication strategy in private cloud environment using Neural Network (NN) Feed Forward and Back Propagation methods. The performance of the propose strategy is analyzed by using a cloud simulator called Cloudsim. A data center, virtual machines and cloudlets are tested for their ability to produce replication by applying Feed Forward NN for pattern recognition, followed by Back Propagation NN to train and produce the Root Mean Square Error. Hence, the Root Mean Square is used to produce data availability and the data availability is used as the triggering factor in this replication strategy. The experimental result shows that the proposed strategy has reduced the response time of replication process and enhanced the availability of the data in cloud computing system.Â Â